2020
DOI: 10.1177/0145561319900388
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Autologous Platelet-Rich Plasma Gel Fat Graft Myringoplasty and the Fat Graft Myringoplasty for the Closure of Different Sizes of Tympanic Membrane Perforations

Abstract: Objective: We aimed to evaluate the effect of autologous platelet-rich plasma gel (PRPG) on fat graft myringoplasty (FGM) in tympanic membrane perforations caused by chronic otitis media. Methods: This retrospective study involved 63 patients who underwent operations between 2015 and 2018. Fat graft myringoplasty was performed with the transcanal approach with and without the use of PRPG in the surgical field. The patients were classified into 2 groups: group A, which included 32 patients who underwent FGM wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…Higher surgical success rates have been reported by all of them in ►Table 5 who used PRP. Ersozlu and Gultekin et al 7 claimed 100% success rates with PRP gel fat graft myringoplasty in 4 months follow-up. However, there was no difference in audiological results.…”
Section: Discussionmentioning
confidence: 99%
“…Higher surgical success rates have been reported by all of them in ►Table 5 who used PRP. Ersozlu and Gultekin et al 7 claimed 100% success rates with PRP gel fat graft myringoplasty in 4 months follow-up. However, there was no difference in audiological results.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 34 nonrepetitive studies identified, eight studies [8][9][10][11][12][13][14][15] including 455 participants with different sizes of TM perforations were eligible for final selection after screening the full texts. These included studies published from 2015 to July 2020 and consisted of five RCTs [9,10,[12][13][14], one prospective study [15], and two retrospective studies [8,11]. Seven of the included studies [8][9][10][12][13][14][15] compared the efficacy of PRP with conventional tympanoplasty or myringoplasty.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…These included studies published from 2015 to July 2020 and consisted of five RCTs [9,10,[12][13][14], one prospective study [15], and two retrospective studies [8,11]. Seven of the included studies [8][9][10][12][13][14][15] compared the efficacy of PRP with conventional tympanoplasty or myringoplasty. Among the seven studies in which the experimental groups received PRP three involved fat graft myringoplasty (FGM) [8,9,14], one used conchal perichondrium myringoplasty (PM) [13], and three involved temporalis fascia tympanoplasty (TFT) [10,12,15].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations